Salmonella contamination in poultry – are we missing a potential reservoir? - Sexton, Ty L., author; Martin, Jennifer N., advisor; Geornaras, Ifigenia, committee member; Belk, Keith E., committee member; Bunning, Marisa, committee member (Colorado State University. Libraries, 2017)
The objective of this study was to assess presence and characteristics of Salmonella enterica found in synovial fluid of broiler carcasses. Synovial fluid of three individual joints from 500 broiler carcasses was individually sampled (1,500 total samples) from five broiler processing facilities located in the Southeast and Western U.S. The external surface of broiler carcass was decontaminated prior to sampling of the shoulder, coxofemoral, and tibiofemoral joints. Individual samples were enriched, composited, and subjected to rapid PCR-based detection of Salmonella. Individual samples from any positive composites were also enriched before determination of Salmonella presence in the same manner. Positive individual samples were subjected to secondary enrichment before plating onto selective agar for isolation of Salmonella. Salmonella isolates were serotyped before determination of antimicrobial susceptibility. Overall, 1.00% (5 out of the 500 broiler carcasses) of composite samples, and 0.47% (7 out of 1,500 samples) of individual samples were positive for Salmonella. Five of the seven isolates were susceptible to all drugs and determined to be Salmonella Enteritidis. The remaining two isolates, identified as Salmonella Typhimurium, were resistant to streptomycin. To our knowledge, no previous assessments of Salmonella in synovial fluid of broilers has been reported; however, results of the present study suggested that Salmonella may be present in synovial fluid of broilers. Although low prevalence, this information provides valuable insight into potential poultry contamination pathways and warrants further exploration.
Keywords: poultry; synovial fluid; Salmonella